Muscle–bone interactions: movement in the field of mechano–humoral coupling of muscle and bone. Issue 1 (1st August 2017) - Cardozo, Christopher P.; Graham, Zachary A.
Abstract: Cyclical, mechanical loading of bone by skeletal muscle is widely recognized as a critical determinant of bone structure and mass. A growing body of evidence indicates that substances released from skeletal muscle into the bloodstream also regulate bone mass and metabolism. In this commentary, we discuss the status of research in the area of humoral regulation of bone mass by the skeletal muscle secretome, with an emphasis on the roles of myostatin, irisin, interleukin‐6, and exosomes. The interplay between muscle, bone, and other modulators of bone mass, including circadian rhythm and sympathetic tone, is also discussed.